Evaluasi Penerimaan Penggunaan Rekam Medis Elektronik oleh Petugas Menggunakan Teori UTAUT 2 - Rohmawati, Siti; Ellina, Agusta Dian; Prasetyo, Joko (Journal of Telenursing (JOTING), 2024)
The aim of this research is to analyze expectancy, effort expectancy, social influence and facilitating conditions on the acceptance of the use of electronic medical records at Hospital X. This research method is quantitative with a cross sectional approach with the data analysis used in this research is the Simple Linear Regression & Moderated Regression Analysis (MRA) test. Based on the results of the analysis of performance expectancy, effort expectancy, and facilitating conditions, the influence on acceptance of the use of electronic medical records is moderated by gender and age. The social influence variable has no effect on acceptance of the use of electronic medical records with moderation by gender and age. From this research, it can be concluded that what influences officers in using electronic medical records is performance expectancy, effort expectancy, and facilitating conditions. RS So that new users can easily understand how the system works. Keywords: Electronic Medical Records. Effort Expectancy, Facilitating Conditions Performance Expectancy, Social Influence